THE IMPACT OF SAMURAI'S SOCIETY ON NATHAN ALGREN IN EDWARD ZWICK'S THE LAST SAMURAI : A BEHAVIOURIST APPROACH - KURNIAWATI , ISNAINI (2006)
This research paper is dealing with one of literary works. The writer takes a movie entitled The Last Samurai as the object of the study. This movie is directed by Edward Zwick and published by Lion Gate, 2003. The writer focuses on the personality of Nathan Algren as a result of the influences of society. The analysis is done by using Behaviorist Approach. After analyzing this movie, the writer finds what the impacts of samurai society on Nathan Algren's personalities. In analyzing the movie, the writer uses qualitative study. There are two kinds of data sources: the primary data are the movie of Edward Zwick's The Last Samurai, while the secondary data are research approach books, fiction study books, and internet websites. The method of collecting data in the research is library research by watching the film, summarizing, paraphrasing, and documenting the data. The technique of data analysis is descriptive analysis. Having analyzed this movie, the writer draws conclusions as follows: First, different cultures can influence individual's personalities. Second, Nathan Algren's personalities are changed because of being influenced by two different cultures, modern culture and traditional culture.